2020
DOI: 10.1038/s41598-020-68040-z
|View full text |Cite
|
Sign up to set email alerts
|

Klf9 is a key feedforward regulator of the transcriptomic response to glucocorticoid receptor activity

Abstract: The zebrafish has recently emerged as a model system for investigating the developmental roles of glucocorticoid signaling and the mechanisms underlying glucocorticoid-induced developmental programming. To assess the role of the Glucocorticoid Receptor (GR) in such programming, we used CRISPR-Cas9 to produce a new frameshift mutation, GR 369-, which eliminates all potential in-frame initiation codons upstream of the DNA binding domain. Using RNA-seq to ask how this mutation affects the larval transcriptome und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 57 publications
8
47
0
Order By: Relevance
“…Another key point of Gr function is related to reproduction, since GCs have been proposed to play a crucial role in this process both in mammals (Whirledge & Cidlowski 2017) and in fish (Faught & Vijayan 2018b). Zebrafish gr homozygous mutants are genetically viable, but their fertility is significantly reduced, in particular with aging (Facchinello et al 2017), a result confirmed also by Gans et al (2020). As hypothesised by Faught & Vijayan (2018b), our analysis on gr ia30/ia30 females confirms that GCs and Gr control ovarian maturation and the ovulation process.…”
Section: Mutants Of Glucocorticoid Receptors In Zebrafishsupporting
confidence: 85%
See 3 more Smart Citations
“…Another key point of Gr function is related to reproduction, since GCs have been proposed to play a crucial role in this process both in mammals (Whirledge & Cidlowski 2017) and in fish (Faught & Vijayan 2018b). Zebrafish gr homozygous mutants are genetically viable, but their fertility is significantly reduced, in particular with aging (Facchinello et al 2017), a result confirmed also by Gans et al (2020). As hypothesised by Faught & Vijayan (2018b), our analysis on gr ia30/ia30 females confirms that GCs and Gr control ovarian maturation and the ovulation process.…”
Section: Mutants Of Glucocorticoid Receptors In Zebrafishsupporting
confidence: 85%
“…The VBA assay is based on the neuroendocrine response determining the shrinkage of zebrafish melanocytes when larvae are exposed to bright background (Kurrasch et al 2009). Nowadays, this test is used in strains defective in the synthesis of GCs for the preliminary selection of homozygous recessive larvae, in which this response is lost (Griffiths et al 2012, Griffin et al 2016, Eachus et al 2017, Facchinello et al 2017, Weger et al 2018, Gans et al 2020, Marchi et al 2020.…”
Section: Mutants Of Glucocorticoid Receptors In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…NR3C1 encodes the glucocorticoid receptor and previous studies have reported that NR3C1 is important for glucocorticoid treatment response in various types of acute leukemia (Haowen et al, 2018;Wandler et al, 2020). KLF9 has been reported as a gene that responds to glucocorticoid signals (Gans et al, 2020;Reddy et al, 2009). It is still unknown how NR3C1 mediates glucocorticoid treatment response in different age groups of infant KMT2A-r ALL.…”
Section: Transcriptomic and Epigenomic Signatures Of Blasts In Youngementioning
confidence: 99%